Augmented reality live demonstrations during traditional lectures improve understanding of computed tomography data sets by medical students - Jacob, Alice M.; Böhner, Alexander M. C.; Beissel, Lucia D.; Oelmeier, Lukas; Born, Mark; Odenthal, Anna-Maria; Endler, Christoph; Henkel, Andreas; Reinert, Matthäus; Nowak, Sebastian; Mesropyan, Narine; Isaak, Alexander; et al. (Frontiers in Virtual Reality, 2025)
IntroductionThe introduction of augmented reality (AR) in medical education has been demonstrated to improve learning of medical students and young clinicians. Use of AR is often linked to Head Mounted Displays (HMD), whose high costs and expertise demands make them less widely applicable.MethodsThe open-source application Medical Imaging XR (MIXR), developed by Medicalholodeck™, was used to visualize computed tomography examinations in augmented reality on mobile devices, including smartphones and tablets. Cases were presented during Radiology lectures. Clinical cases relevant to each lecture topic—thorax, abdomen, gynecology, musculoskeletal system, and emergency medicine—were selected from our local picture archiving system. The cases were demonstrated on mobile devices during a radiological lecture, either in person or via video conference. To evaluate the educational experience, students provided feedback through a structured questionnaire.ResultsMedical students received a demonstration with AR in the lecture and were asked to answer a questionnaire. 47 students replied to the questionnaire. Students rated their experience with MIXR in a positive manner. 36.2% of students considered AR images to be very comprehensible, whereas only 21.3% considered conventional images as very comprehensible. 32 out of 47 considered that AR demonstration contribute to better understanding of the case as whole. 91.8% of students would like to continue using AR in the studies and 80.9% would like to have similar tools available for future interactions with patients.Conclusion/DiscussionIntroduction of AR in radiology lectures is well received by medical students, who would be interested in continuing using AR tools in their studies and future career. Using mobile device-based AR proved viable, contributing to democratization of AR, in a low-cost manner and with no need for extended expertise.